2010
DOI: 10.1002/chem.201002265
|View full text |Cite
|
Sign up to set email alerts
|

Ostensible Enzyme Promiscuity: Alkene Cleavage by Peroxidases

Abstract: Enzyme promiscuity is generally accepted as the ability of an enzyme to catalyse alternate chemical reactions besides the 'natural' one. In this paper peroxidases were shown to catalyse the cleavage of a C=C double bond adjacent to an aromatic moiety for selected substrates at the expense of molecular oxygen at an acidic pH. It was clearly shown that the reaction occurs due to the presence of the enzyme; furthermore, the reactivity was clearly linked to the hemin moiety of the peroxidase. Comparison of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
0
14
1
Order By: Relevance
“…The authors propose the term ostensible promiscuity for this observation. [39] This paper reviews enzyme catalytic promiscuity from a biocatalytic perspective. In the first part, the fundamentals of enzyme catalytic promiscuity are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors propose the term ostensible promiscuity for this observation. [39] This paper reviews enzyme catalytic promiscuity from a biocatalytic perspective. In the first part, the fundamentals of enzyme catalytic promiscuity are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these peroxidase catalyzed reactions (according to Scheme 8) [22] do not proceed to a significant extent when the peroxidase is replaced by 1, which indicates that the Fe III -porphyrin-catalyzed transformation is highly chemo-selective (Scheme 7). The overoxidation of para-anisaldehyde 4 to its carboxylic acid was also not reported with 1 as a catalyst.…”
Section: Fetspp (1) As Oxidation Catalyst In Organic Synthesesmentioning
confidence: 95%
“…Kroutil et al found that here cleavage of the bond or dihydroxylation was observed in the biotransformation of trans-anethol 2 when using different types of peroxidases (Scheme 8). [22] In this reaction, besides para-anisaldehyde 4 as major product also the resulting 1,2-diol 6 was obtained.…”
Section: Fetspp (1) As Oxidation Catalyst In Organic Synthesesmentioning
confidence: 98%
“…Care has also to be taken, that the apparent promiscuous reaction de facto stems from enzymatic catalysis and is not chemically catalyzed by a prosthetic group only [81] or by amino acids not related to an active site (e.g. EstB from B. gladioli , [82]) or from an apparent new reaction due to an overlooked change of the actual substrate e.g.…”
Section: Active Site (Re)designmentioning
confidence: 99%